2022
DOI: 10.3390/catal12070698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Iron Phases of Fe/SiO2 Catalyst in CO2 Hydrogenation under Mild Conditions

Abstract: The effect of different active phases of Fe/SiO₂ catalyst on the physio-chemical properties and the catalytic performance in CO₂ hydrogenation under mild conditions (at 220 °C under an ambient pressure) was comprehensively studied in this work. The Fe/SiO₂ catalyst was prepared by an incipient wetness impregnation method. Hematite (Fe₂O₃) in the calcined Fe/SiO₂ catalyst was activated by hydrogen, carbon monoxide, and hydrogen followed by carbon monoxide, to form a metallic iron (Fe/SiO₂-h), an iron carbide (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Secondly, through CO 2 -TPD, the doping of Ca will weaken the catalyst's basicity but increase the catalyst's basic sites, especially when the Ca doping amount is 1 mmol. The increased basic sites are more conducive to the adsorption of CO 2 , and the red CO 2 in the figure indicates additional CO 2 * Finally, according to the previous literature, [49][50][51] the increase of basic sites benefits the hydrogenation of CO 2 * Therefore, the doping of Ca further improves the performance of the Zn10Fe20 catalyst, and the improvement is most apparent when the doping amount of Ca is 1 mmol.…”
Section: Catalysts X Co2 [%] S Co [%]mentioning
confidence: 63%
See 3 more Smart Citations
“…Secondly, through CO 2 -TPD, the doping of Ca will weaken the catalyst's basicity but increase the catalyst's basic sites, especially when the Ca doping amount is 1 mmol. The increased basic sites are more conducive to the adsorption of CO 2 , and the red CO 2 in the figure indicates additional CO 2 * Finally, according to the previous literature, [49][50][51] the increase of basic sites benefits the hydrogenation of CO 2 * Therefore, the doping of Ca further improves the performance of the Zn10Fe20 catalyst, and the improvement is most apparent when the doping amount of Ca is 1 mmol.…”
Section: Catalysts X Co2 [%] S Co [%]mentioning
confidence: 63%
“…It is evident that the Zn10Fe20 catalyst without Ca doping has three desorption peaks at 100, 670, and 790 °C, respectively, corresponding to weak, medium, and strong basic sites. [49] With the doping of Ca, the peak at the weak alkaline site shows an interesting change. On the one hand, the doping of Ca shifted the low-temperature desorption peak to the left, and the less the doping of Ca, the more it moved to the left, which indicated that the doping of Ca further weakened the weak basicity of the Zn10Fe20 catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As observed in Figure 2f, all the catalysts show desorption peaks in the temperature range of 350−800 °C in the H 2 -TPD profile, which are assigned to the decomposition of CH species as well as the splitting of OH species. 29,30 The H 2 -TPD pattern of Na/Fe shows three desorption peaks at 403, 562, and 628 °C. The Na/Fe@FeCo-P 0.1 catalyst exhibits higher desorption temperature of H species than Na/Fe, indicating that the introduction of FeCo PBA inhibited the decomposition of CH species.…”
Section: Morphology and Structurementioning
confidence: 99%